Trade and investment rule-making the role of regional and bilateral agreements - Woolcock, Stephen; United Nations University. UNU-CRIS. (Tokyo United Nations University Press, 2006)
"Regional trade agreements are playing a greater role in shaping trade and investment rules around the world. To date the study of preferential agreements has focused on their impact on tariff preferences, but as tariffs are reduced rule-making becomes more important in trade and investment. This book addresses the role of regional and bilateral agreements in rule-making; provides an analytical framework for assessing the impact of regional and other preferential agreements on rule-making; and illustrates the role of regional agreements in a multi-level process of rule-making.--Publisher's description."--From source other than the Library of Congress
"UNU-CRIS"--P. facing t.p.
Keywords: Trade blocs; International trade; Foreign trade regulation; Regional economics